ANALISA KAPASITAS APRON TERHADAP ON TIME PERFORMANCE PADA SAAT PEAK HOURS DI BANDAR UDARA INTERNATIONAL HANG NADIM BATAM - Kevin Azcha El Sulthany; Kukuh Tri Prasetyo; Sudrajat (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The apron capacity at Batam's Hang Nadim International Airport is very limited. The increasing surge in passengers resulted in an increase in scheduled commercial flights. So that flight activity, especially in the apron, is getting denser. During peak hours, it can be indicated that the apron's capacity is unable to accommodate the annual increase in aircraft movements. This of course has a very significant impact, namely flight delays (flight delays) that occur almost every day, queues to land and take off which can cause losses to the airline so that it has an impact on the airport's On Time Performance (OTP). This can be shown by the increasing number of passenger movements and aircraft operated, which in turn will lead to a significant increase in the number of flight frequencies. The frequency of flights at Batam's Hang Nadim International Airport increases every year. This indicates the number of flight activities at the airport, starting from planes that will land and take off so that there are certain times that indicate peak hours.